Pengaruh Teknik Effleurage Terhadap Penurunan Skala Nyeri Involusi Uteri Pada Ibu Post Partum Hari Ke-1 Di UPT Puskesmas Buay Pemaca - Nely Alfiyani; Winarni (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Unpreparedness physically, psychologically, mentally and spiritually in facing this period will make mothers experience problems related to involution and postpartum pain. Many things are risk factors for failure of involution and lactation. These factors include mobilization, nutrition, lactation, environmental, cultural and family factors. Objective: To determine the effect of effleurage massage on reducing the pain scale due to uterine involution in postpartum mothers on day 1. Research Location: UPT Buay Pemaca Health Center. Research Method: Quantitative research type with a pre-experimental design type one group pretest and posttest. Results: Almost all postpartum mothers before being given effleurage massage experienced uterine involution pain on a moderate pain scale of 19 people (95%), more than half of postpartum mothers after being given effleurage massage experienced uterine involution pain on a moderate pain scale of 12 people (60 %), there is an influence of the Effluurge Massage Technique on Reducing the Pain Scale of Uterine Involution in Post Partum Mothers on Day 1. Conclusion: Effleurage massage can reduce the level of uterine involution pain in postpartum mothers.